Impact evaluation of improved nutrition through integrated basic social services and social cash transfer pilot program (IN-SCT) in Oromia and SNNP regions, Ethiopia: Endline impact evaluation report - Gilligan, Daniel O.; Arrieta, Alejandra; Devereux, Stephen; Hoddinott, John F.; Kebede, Dereje; Ledlie, Natasha; Roelen, Keetie; Taffesse, Alemayehu Seyoum (United Nations Children's Fund, 2020)
In 2015, UNICEF in collaboration with the Ministry of Labor and Social Affairs (MoLSA) introduced the Integrated Nutrition–Social Cash Transfer (IN-SCT) pilot program in Oromia and SNNP Regions of Ethiopia, through funding from Irish Aid. The IN-SCT program aims to support and enhance the implementation of Phase 4 of the Productive Safety Net Program (PSNP4) by providing an integrated package of multisectoral nutrition services and engaging in activities to strengthen the quality of health services offered. The International Food Policy Research Institute (IFPRI), Institute of Development Studies (IDS) at University of Sussex, and Cornell University conducted an impact evaluation of the IN-SCT program. A baseline survey for the impact evaluation, including both quantitative and qualitative components, was conducted from March–May 2016 in SNNP and Oromia regions. A qualitative midline survey was conducted in March–April 2017. For the endline survey, the qualitative component was conducted in March–April 2018 and the quantitative component was conducted from August–September 2018.